2019
DOI: 10.1186/s12909-019-1521-2
|View full text |Cite
|
Sign up to set email alerts
|

Stress and stressors of medical student near-peer tutors during courses: a psychophysiological mixed methods study

Abstract: Background Structured peer-led tutorial courses are widespread and indispensable teaching methods that relieve teaching staff and contribute to the development of students’ competencies. Nevertheless, despite high general stress levels in medical students and associated increases in psychopathology, specific knowledge of peer tutors’ additional burdens is very limited. Methods Sixty student near-peer tutors from two structured peer-teaching programmes volunteered to par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 104 publications
4
10
0
1
Order By: Relevance
“…Several students autonomously identified repetitive practice as a means to overcome this anxiety. Peer-teaching in other settings has been documented to cause anxiety in the peer-teacher, which was also reported by our participants [12][13][14]. Though similar to previous studies, our participants reported that this decreased during the preparation.…”
Section: Competenceovercoming Fearsupporting
confidence: 91%
See 2 more Smart Citations
“…Several students autonomously identified repetitive practice as a means to overcome this anxiety. Peer-teaching in other settings has been documented to cause anxiety in the peer-teacher, which was also reported by our participants [12][13][14]. Though similar to previous studies, our participants reported that this decreased during the preparation.…”
Section: Competenceovercoming Fearsupporting
confidence: 91%
“…Though similar to previous studies, our participants reported that this decreased during the preparation. It has also been reported in the literature that as more PAL activities are established in curricula that this learner anxiety reduces and that peer-teaching prepares students for future careers/roles as clinician-teachers and medical educators [ 12 , 14 ]. The anxiety experienced by students preparing for peer-teaching activities in the peer-teaching model needs to be addressed with adequate supervision, where available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we should draw attention to the increased risk of burnout if PAL is intended to be widely used in clinical teaching. Same concern was also raised by other researchers, Hundertmark et al comprehensively quantified tutors’ stress and described frequent stressors in the PAL [ 39 ], and Matthew et al proposed that support and feedback developed competence and confidence and reduced stress and anxiety [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies show that tutors are able to convey skills and knowledge as effectively as faculty staff [22][23][24]. Further recognized benefits of using peers as teachers include cognitive, social, and economic benefits, as well as the acquisition of teaching, organizational, and interpersonal competencies for peer tutors themselves [20,[25][26][27][28]. In general, peer-teaching is well established in health professions, especially in nursing education [29,30].…”
Section: Introductionmentioning
confidence: 99%